Hermeneutics in Paul Ricoeur as a Way of Interpreting Cultural Symbolic Language and Human Interaction with the Environment - Silva, Thiago Souza; Quadros, Elton Moreira (Revista Nacional de Gerenciamento de Cidades, 2020)
This present work intends to prospect the potential of hermeneutics in the point of view of Paul Ricoeur, as a viable proposal to understand culture, considered as a human formation filled with symbolic language. While formulating this method, Ricoeur uses concepts developed by psychoanalysis as foundation in order to study the human meaning it involves, so that the aim of the theory of interpretation includes the action of demonstrating that reality is symbolic and needs to be interpreted as such. We also worked to facilitate a dialogue regarding the environment, pursuing a concept that goes beyond the understanding of the physical environment, and encompasses the social and cultural dimensions of its constitution. We accomplished, therefore, an interdisciplinary bibliographical research where we demonstrate that human beings are by excellence promoters of culture, but also products of it. Culture supplies human beings with the resources that are indispensable for their interaction with nature, and therefore, disseminates the principles that establish behavioral patterns, which are mediated by symbols. Thus, we concluded that human beings are immersed in a cultural and environmental context governed by symbols, and that, from this presumption, the symbols construct meanings connected to existence.